Maternal and Perinatal Outcome of Hypertensive Disorders of Pregnancy In a Tertiary Hospital of Kathmandu - Paudel, Narayani; Shrestha, Santoshi; Parajuli, Puspa (Journal of Kathmandu Medical College, 2018)
Background: Hypertensive disorders of pregnancy are considered to be a major worldwide health problem causing an increased risk of perinatal and maternal morbidity and mortality. Hypertensive disorders are the most common medical disorders encountered during pregnancy. Objective: This study aimed to assess the maternal and perinatal outcome of hypertensive disorders in pregnancy. Methods: A hospital based prospective study was conducted in Obstetrics ward of Kathmandu Medical College Teaching Hospital. Total one hundred pregnant women admitted in antenatal ward with the diagnosis of hypertensive disorders in pregnancy were included in the study. A structured questionnaire was designed and data collection was done through one- to- one interview technique during the period of December 2015 to January 2017. The collected data were analyzed by using Statistical Package for Social Science version 20. Results: Among 100 hypertensive disorders; 80% respondents had gestational hypertension, 16% had preeclampsia and two percent had eclampsia. Of total, 52% respondents had normal vaginal delivery followed by 46% caesarian section. One respondent had ante-partum hemorrhage, 11% had post-partum hemorrhage and one had developed hemolysis, elevated liver enzymes low platelets counts syndrome. Fortunately, no maternal mortality was occurred. Regarding perinatal outcome, 17% babies were born preterm, 13% babies had low birth weight and seven percent babies had birth asphyxia. Total fi ve were stillbirths and one percent had early neonatal death. Conclusion: Maternal outcome was good except few morbidities but perinatal outcome was found to be adverse. Proper management of hypertensive disorders is required to reduce perinatal morbidities and mortalities. Journal of Kathmandu Medical College, Vol. 6, No. 4, Issue 22, Oct.-Dec., 2017, Page: 145-149